Cruising Comfortably? A Qualitative Insight Into Liveaboard Tourism In Labuan Bajo, Indonesia - Jussac Maulana Masjhoer; Aditha Agung Prakoso (Ministry of Tourism Republic of Indonesia, 2026)
Labuan Bajo, the primary gateway to Indonesian marine tourism, faces significant safety challenges due to the rapid growth of its liveaboard industry. This study examines a two-day, one-night liveaboard experience on open-deck boats, focusing on regulatory compliance and the gap between comfort amenities and safety procedures. Employing a descriptive qualitative methodology, data were collected through interviews with operators, regulators, and tourists, as well as participant observation. The findings reveal a pronounced safety-comfort paradox: operators consistently meet tourist expectations regarding tangible aspects such as deck aesthetics, cleanliness, and food presentation, yet systematically fail to comply with mandatory maritime safety standards. These failures include the absence of fire extinguishers, safety information boards, and consistent pre-departure safety briefings. Cognitive biases in risk appraisal among both operators and tourists, combined with inadequate regulatory enforcement by port authorities, further exacerbate this issue. This study contributes to the maritime risk management literature by demonstrating that perceived comfort can overshadow risk perception in emerging tourism destinations. It is recommended that operators integrate safety protocols into the voyage's experiential narrative and that maritime authorities conduct random onboard inspections to strengthen safety culture in Indonesia's mid-range liveaboard industry.